L-Lactide polymerization studied by 1H NMR with diffusion-ordered spectroscopy (DOSY): a "One NMR Tube Experiment" providing data on monomer conversion, polymer structure, Mn and Mw1. Issue 24 (28th June 2015) - Lewinski, P.; Sosnowski, S.; Kazmierski, S.; Penczek, S.
<x xml:space="preserve">Abstract</x> The standard NMR and DOSY techniques allowed for the first time the on-line study of the polymerization kinetics together with the determination of number average molar mass Mn and mass average molar mass Mw.